Human Rights During the Pandemic: COVID-19 and Securitisation of Health. Issue 3 (3rd July 2021) - Gozdecka, Dorota Anna
ABSTRACT: This article analyses the response to the COVID-19 pandemic and its securitising effect on health and human rights globally. It asks whether measures taken to control the pandemic comply with the emergency provisions and limitations allowed under human rights treaties, and whether they will lead to more permanent securitisation of the health sector. It examines the impact of some pandemic control measures introduced in Western countries on human rights to answer the question of how the latter will be affected long-term.